Recent discoveries and advancements in research on the Lyme disease spirochete Borrelia burgdorferi - Winslow, Christa (F1000 Research Limited, 2019)

(untitled) (F1000Res)
This review highlights some of the highest-profile developments and advancements in the research on Borrelia burgdorferi, the Lyme disease spirochete, that have emerged in the last two years. Particular emphasis is placed on the controversy surrounding genus nomenclature, antigenic variation at the vlsE locus, genes involved in infectivity and virulence, membrane characteristics of B. burgdorferi, and developments in experimental approaches.